The Physiology of Exercise in Spinal Cord Injury - Taylor, J. Andrew (Physiology in Health and Disease,, 2016)
Every year, around the world, between 250,000 and 500,000 people suffer a spinal cord injury (SCI). Those with an SCI are two to five times more likely to die prematurely than people without a spinal cord injury, with worse survival rates in low- and middle-income countries. Dynamic aerobic requires integrated physiologic responses across the musculoskeletal, cardiovascular, autonomic, pulmonary, thermoregulatory, and immunologic systems. Moreover, regular aerobic exercise beneficially impacts these same systems, reducing the risk for a range of diseases and maladies. This book will present comprehensive information on the unique physiologic effects of SCI and the potential role of exercise in treating and mitigating these effects. In addition, it will incorporate work from scientists across a number of disciplines and have contributors at multiple levels of investigation and across physiologic systems. Furthermore, SCI can be considered an accelerated form of aging due to the severely restricted physical inactivity imposed, usually at an early age. Therefore, the information presented may have a broader importance to the physiology of aging as it relates to inactivity. Lastly, the need for certain levels of regular aerobic exercise to engender adaptations beneficial to health is not altered by the burden of an SCI. Indeed, the amounts of exercise necessary may be even greater than the able-bodied due to 'passive' ambulation. This book will also address the potential health benefits for those with an SCI that can be realized if a sufficient exercise stimulus is provided.